Could Gender Self-determination be a Medical Right? - Barros, Marcos García de (Science Insights, 2024)
It is crucial to evaluate the potential risks and repercussions of advocating for gender self-determination as a medical right. The concept of permitting individuals to determine their own gender without proper assessment or counseling raises concerns about patient safety and well-being, despite the fact that autonomy and self-determination are essential in healthcare decision-making. Gender dysphoria, a recognized psychiatric condition, necessitates a comprehensive evaluation by trained professionals to guarantee the most suitable diagnosis and treatment. Negative physical and psychological consequences may arise from permitting individuals to make irreversible decisions, such as hormone therapy or surgery, without adequate supervision. Furthermore, medical guidelines are in place to guarantee that patients receive evidence-based care that is consistent with the most effective transgender health practices. Consequently, it is pivotal for healthcare providers to exercise caution when it comes to gender self-determination and to prioritize the comprehensive care of transgender individuals by providing comprehensive support services, rather than relying solely on individual autonomy.